2003
DOI: 10.1046/j.1523-1755.2003.00237.x
|View full text |Cite
|
Sign up to set email alerts
|

Urinary and renal interstitial concentrations of TNF-α increase prior to the rise in albuminuria in diabetic rats

Abstract: We found an early rise in renal TNF-alpha levels after induction of diabetes with STZ, which precedes the rise in UAE by about 2 weeks. These findings suggest a possible contribution of TNF-alpha in the complicated pathogenic process resulting in microalbuminuria in diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
121
1
2

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 156 publications
(137 citation statements)
references
References 26 publications
13
121
1
2
Order By: Relevance
“…Additionally, many studies have shown that changes in hormone levels, vasoactive peptides, cytokine, and growth factors are associated with diabetic nephropathy development and progression. Specifically, rat studies have suggested a functional role for the proinflammatory cytokine tumor necrosis factor (TNF)-␣ in the pathogenesis of diabetic nephropathy (19,20). Supporting this finding are intervention studies in patients with either diabetic or membranous nephropathy that found that the nonspecific TNF-␣ inhibitor pentoxifylline reduced both TNF-␣ and urinary proteinura (21,22).…”
Section: Drb1*04 and Reduced Diabetic Nephropathysupporting
confidence: 53%
“…Additionally, many studies have shown that changes in hormone levels, vasoactive peptides, cytokine, and growth factors are associated with diabetic nephropathy development and progression. Specifically, rat studies have suggested a functional role for the proinflammatory cytokine tumor necrosis factor (TNF)-␣ in the pathogenesis of diabetic nephropathy (19,20). Supporting this finding are intervention studies in patients with either diabetic or membranous nephropathy that found that the nonspecific TNF-␣ inhibitor pentoxifylline reduced both TNF-␣ and urinary proteinura (21,22).…”
Section: Drb1*04 and Reduced Diabetic Nephropathysupporting
confidence: 53%
“…We also found that serum and urinary TNF-α levels were significantly higher in macroalbuminuric and microalbuminuric group compared to normoalbuminuric patients, similar results detected by Kalantarinia et al, (2003) they showed higher serum TNF-α levels both in macroalbuminuric and in microalbuminuric compared with normoalbuminuric patients [27]. In agreement with our results also, Wong et al, (2007) reported that the serum and urinary concentrations of TNF-α were elevated in DN as compared with non-diabetic individuals or with diabetic subjects without kidney disease and that these concentrations increase concomitantly with the progression of DN.…”
Section: Similar To Our Results Molitch Et Al (2004)supporting
confidence: 78%
“…However, TNFa levels showed a close relationship with Hcy levels. In a study, urinary and interstitial TNFa concentrations were shown to be elevated in diabetic rats before the commencement of microalbuminuria (31). This finding suggests that TNFa may have a role in the complex pathogenesis of diabetic nephropathy.…”
Section: Discussionmentioning
confidence: 79%